Advances in Crowdfunding 2020
DOI: 10.1007/978-3-030-46309-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding in Europe: Between Fragmentation and Harmonization

Abstract: The European crowdfunding market is growing rapidly, especially in continental Europe. At the same time, cross-border activities are still constrained. Fragmented markets, especially caused by differences in regulation, are an obstacle to growth of crowdfunding platforms. The European Union introduced the European Crowdfunding Service Provider (ECSP) Regime in 2019. This harmonized regime applies to crowdfunding platforms intermediating equity and debt investments between businesses and retail investors. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…3. Existence of self-regulation and codes of conducts adhered to by the platforms-Gromek refers to the Code of Conduct the UK Crowdfunding Association, which has also been formative for other Codes of Conduct in Europe (Odorović and Wenzlaff 2020). 4.…”
Section: Existence Of Crowdfunding Associations-gromek Refers To the ...mentioning
confidence: 99%
“…3. Existence of self-regulation and codes of conducts adhered to by the platforms-Gromek refers to the Code of Conduct the UK Crowdfunding Association, which has also been formative for other Codes of Conduct in Europe (Odorović and Wenzlaff 2020). 4.…”
Section: Existence Of Crowdfunding Associations-gromek Refers To the ...mentioning
confidence: 99%
“…The European Parliament has highlighted the diversity of crowdfunding regimes in the Member States as a crucial factor which rendered crowdfunding business models less easily 'passportable' across the EU (European Parliament, 2018). One of the most significant "pre regulation" discussions was about the fragmented regulatory landscape within the EU, which leaded to the fact, that platforms operate mainly in the country of registration (Wenzlaff, Odorovic et al, 2020). However, some studies have shown high performance of cross-border financing of crowdfunding platforms of the Baltic States (Ziegler, Shneor, et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, crowdfunding is a well-established concept in Finland with some 20 active platforms already operating in the market, while jointly overseeing volumes surpassing 390 million USD in 2020 (Ziegler et al, 2021). And third, Finland was one of the first European countries to introduce regulatory amendments in support of a crowdfunding market development, well before the introduction of the European Crowdfunding Service Provider regime (Wenzlaff et al, 2020).…”
Section: Introductionmentioning
confidence: 99%